SIMULASI DAN MONITORING KOORDINASI RECLOSER DAN SSO PADA JARINGAN DISTRIBUSI 20 KV PT. PLN (PERSERO) AREA SEMARANG PENYULANG KALISARI 07 BERBASIS ARDUINO MEGA 2560 DAN VT SCADA 11.2 - Zuraida, Hanif; Winarno, Heru (Gema Teknologi, 2019)
Â Hanif Zuraida, Heru Winarno, in this article describes the simulation of protection equipment coordination systems, especially in the recloser and sectionalizer areas. Coordination between protective equipment to improve the network reliability system so that in the event of a disturbance, the area affected by the disturbance does not spread widely. The simulation tool is made using OMRON LY2N 12V relay, ULN2803 relay driver circuit, ZMCT103C current sensor, voltage divider voltage sensor, pull down, 12V 6W lamp as a load and several resistors with different resistivity values as interference. Arduino Mega 2560 is used as the central controller for the entire circuit. After the experiment, the results obtained are when the normal network current at the recloser is 0.86 A and the current at the LBS SSO1 is 0.43. The recloser and LBS SSO1 coordination lies in zone 2 and 3 disturbances. When simulated zone 2 interference, the recloser current rises to 1.28 A, causing reclose / trip to lock out recloser. When the recloser feels a fault current in zone 3 of 1.06 A and LBS SSO1 senses a current of 0.64 A. The recloser as protective equipment will open first within 1000 ms after sensing the disturbance. When the recloser opens, the voltage on the SSO will be 0 volts and the SSO will open within 1000 ms after the current and disturbance requirements are met. Then the recloser will close again after 2000 ms from the open condition.